Kardiochirurgia dorosłychAortic valve-sparing operation in patients with aneurysms of the aortic root and ascending aorta – early and mid-term results - Siudalska, Hanna; Szpakowski, Eugeniusz; Sitko, Tadeusz; Wojno, Anna; Klisiewicz, Anna; Biederman, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Aortic valve sparing operations were developed to preserve the native aortic valve in patients with relatively normal aortic cusps and aortic root aneurysms with or without aortic insufficiency secondary to dilatation of the sinotubular junction or annulus. These operations are an alternative to replacement of the aortic valve and ascending aorta using a conduit containing a tissue or mechanical valve, which has been considered the standard operation to treat patients with aortic root aneurysm. An important feature of this method is the absence of the need for anticoagulation treatment and lack of other complications resulting from mechanical prosthesis implantation. Aim: The aim of this study was to determine the early and mid-term results of aortic valve reimplantation to treat aortic root and ascending aorta aneurysm. Material and Methods: From 2001 to 2008, 45 patients (male 32, female 13) underwent aortic valve sparing operations for aortic root aneurysms (10 patients) and aortic root with ascending aorta aneurysms (35 patients). Their mean age was 45.5±17.1 years. In all patients the reimplantation technique was used. Mean early follow-up was performed 21.1±9.1 days and at mid-term, 21.9±16.1 months after the operation. Severe aortic insufficiency (AI) was diagnosed in 31.1% of patients (n=14), moderate in 42.2% (n=19) and mild 26.6% (n=12). 8 patients had Marfan’s syndrome, 8 patients had bicuspid aortic valve, in 22 patients hypertension was diagnosed and in 4 patients aortic dissection was noted. The tube graft was implanted using pledged sutures at the level of the aortic root and with reimplantation of coronary ostia to the tube graft. During the operation transoesophageal echocardiographic assessment of the reimplanted aortic valve function was performed. Early and mid-term results of the operation were assessed on the basis of transthoracic echocardiographic study. Quality of life (QoL) was evaluated using the Nottingham Health Profile (NHP) form. Results: In the transoesophageal echocardiographic examination no significant AI was revealed. Early echocardiographic assessment revealed 89.9% of patients free from moderate or severe AI. In mid-term observations 7 had developed moderate AI (15.5%) and 1 severe AI (2.2%). 82.3% of patients were free from significant AI. Freedom from aortic valve reoperation at 8 years was at the level of 97.8%. There were two hospital deaths. One was on the 20th postoperative day in a patient with severe AI and with III/IV NYHA heart failure. He underwent kidney transplantation, had severe kidney failure and required chronic dialysis. The second patient, with acute aortic dissection, died on the 10th postoperative day, because of heart failure. An additional death was registered due to leukaemia two years after the operation. One female became pregnant after the operation and delivered successfully by vaginal delivery. QoL in all six sections of NHP – energy, physical mobility, emotional reactions, pain, sleep and social isolation – was assessed as very good (60–100 points). Conclusions: Early and mid-term observation of patients treated because of aortic root aneurysms with the used reimplantation technique revealed good results of the operation and high quality of life.